Potential natural carotenoid sources for the colouration of ornamental fish: a review - Sathyaruban, S.; Uluwaduge, D.I.; Yohi, S.; Kuganathan, S. (University of Jaffna, 2021)
Attractive colouration of ornamental fishes is an important quality criterion in the aquarium fish industry. Ornamental fish cannot synthesize colour-producing carotenoid pigments and therefore must rely on dietary carotenoids in natural or synthetic forms to achieve their colour pigmentations. The aim of this review is to compile and summarize recent investigations into different carotenoid sources used in ornamental fish feed formulations and to highlight the research gaps and investigation needs in the field of aquaculture. The natural carotenoid sources which have been widely used for enhancing colouration are non-photosynthetic organs of higher plants, microalgae, seaweeds, crus tacean by-products, and red yeast. Consumers mostly prefer to use natural sources rather than synthetic sources. The problem faced by aquaculturists is stabilization of the gained skin colour after terminating feeding of the fish. Advanced investigations are needed to identify the stability of the colouration in the ornamental fish during their life cycle. Further, this review encourages the use of other available natural carotenoid sources in the ornamental fish industry in order to reduce the use of synthetic pigment products and invites research to be done on a genetic level in order to fully understand colour distribution patterns and sustainability of colouration gain.
Keywords: Algae; Carotenoid pigments; Colouration; Crustacean waste; Non-photosynthetic organs in higher plants; Ornamental fish feed